(untitled) (Journal of Health Sciences, 2015)
Introduction: The integral part of the treatment of pediatric oncological patients is a range of diagnostic and therapeutic procedures. These procedures are often associated with the fear and anxiety of the suffering child. We investigated whether a psychological preparation through drama therapy and the therapeutic puppet may reduce the anxiety related to diagnostic and therapeutic procedures in the preschool or early school children suffering from cancer.Methods: Twenty consecutive pediatric patients of preschool and early school age, with the diagnosis of lymphoblastic leukemia, were included in the study. The patients were alternatingly assigned to experimental or control group, and subjected or not subjected to drama therapy, respectively. We measured the changes in heart rate, blood pressure and respiratory rate as indicators of anxiety and fear, before and after the diagnostic or therapeutic procedures.Results: Heart rate, blood pressure, and respiratory rate in pediatric oncological patients before and after the diagnostic or therapeutic procedure were significantly lower in the experimental group of patients.Conclusion: Our results show that psychological preparation using drama therapy and therapeutic puppet reduced the fear and anxiety related to diagnostic or therapeutic procedures in pediatric oncological patients.Key words: drama therapy; therapeutic puppet; children; oncology; psychology